Noncovalent self‐assembled supramolecular aggregate decorated nickel‐aluminum layered double hydroxides nanosheets for reinforcing the flame retardancy of PLA. Issue 17 (21st February 2023) - Wang, Kunyan; Jiang, Yuqi; Lv, Changjin; Chi, Qianhui; Guo, Yuhua; Tang, Peisong; Pan, Guoxiang; Guo, Qipeng
Abstract: In this work, an environmentally friendly and energy‐saving strategy to decorate Ni‐Al layered double hydroxides nanosheets (LDHs@PN) has been utilized to boost their flame retardancy and dispersion in the polymer. This proposed strategy was implemented through noncovalent self‐assembly supramolecular aggregate of phytic acid (PA) and 1, 4‐bis(3‐aminoethyl) piperazine (AEP) onto NiAl‐LDHs surface in water without any organic solvent. The target product LDHs@PN was investigated by different characterization techniques. It was found that LDHs@PN was successfully fabricated possessing hydrophobic surfaces. In contrast, the surface of LDHs@PN became rough and exhibited a fluffy structure. Meanwhile, Ni, Al, P and N were homogeneously distributed on the surface of LDHs@PN. Significantly, after introducing LDHs@PN into biobased polylactic acid (PLA) via melting‐blending, the thermal stability of composites was improved compared to that of pure PLA and LDHs@PN promotes the formation of composite residual carbon. In addition, the PLA/LDHs@PN composite with 20 wt% loadings reached V‐0 rating in the UL‐94 test and achieved 30.1% limiting oxygen index value, indicating LDHs@PN significantly increased the flame retardant performance of the PLA. The flame retardant mechanism of LDHs@PN in the PLA matrix was analyzed. This facile, low‐cost and eco‐friendly decorating strategy is promising for industrial production. Abstract :